2016
DOI: 10.1111/opn.12137
|View full text |Cite
|
Sign up to set email alerts
|

Essential elements of the nursing practice environment in nursing homes: Psychometric evaluation

Abstract: The valid subscales of the Essentials of Magnetism II instrument can be used to design excellent nursing practice environments that support nurses' delivery of care. Before using the entire instrument, however, the other subscales have to be improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Factors that related to a supportive practice environment of RNs included being involved in facility affairs and decision-making, having a supportive manager, and having adequate resources (e.g., be adequately staffed to spend enough time with residents). In a study conducted in Dutch nursing homes, which measured the practice environment with the Essentials of Magnetism II © instrument, the researchers concluded that all measured elements of magnetism (e.g., having clinically competent peers, collaborative nurse-physician relationship, having clinical autonomy, receiving manager support, having control over nursing practice) could be considered relevant for the nursing home setting (de Brouwer et al, 2017). Our findings are in line with both studies, suggesting that in addition to focusing on the particular roles of RNs in nursing homes, it is also important to invest in the practice environment.…”
Section: Discussionmentioning
confidence: 99%
“…Factors that related to a supportive practice environment of RNs included being involved in facility affairs and decision-making, having a supportive manager, and having adequate resources (e.g., be adequately staffed to spend enough time with residents). In a study conducted in Dutch nursing homes, which measured the practice environment with the Essentials of Magnetism II © instrument, the researchers concluded that all measured elements of magnetism (e.g., having clinically competent peers, collaborative nurse-physician relationship, having clinical autonomy, receiving manager support, having control over nursing practice) could be considered relevant for the nursing home setting (de Brouwer et al, 2017). Our findings are in line with both studies, suggesting that in addition to focusing on the particular roles of RNs in nursing homes, it is also important to invest in the practice environment.…”
Section: Discussionmentioning
confidence: 99%
“…The original scale contains 11 items. Previous research indicated that the original scale had an acceptable Cronbach Alpha of 0.70, but contained two to three factors (Brouwer et al, 2014;Brouwer, Kaljouw, Schoonhoven, & Achterberg, 2017). The selected four items measure clinical autonomy in terms of perceived limited freedom to make care-related decisions.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, White and colleagues (2008) addressed supportive relationships, which focused on friends and family, but did not include the relationships between residents and staff in their Person-Directed Care Measure [ 27 ]. Other tools have incorporated items on the staff–resident relationship [ 20 , 22 , 23 ], further strengthening the importance for inclusion. Table 2 provides an overview of supporting references for the items [ 21 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…A literature search revealed additional assessment tools specific to long-term care/nursing homes ( Table 1 ) [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Despite the availability of these instruments, some overall concerns must be noted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation